Asepsis medical & surgical techniques - University of Calgary. Faculty of Nursing (Ontario : University of Calgary, 1997)
This CD-ROM instructional program focuses on the use of aseptic principles in the medical and surgical environment and will assist the learner in understanding the techniques required to prevent the spread of microorganisms
System requirements: Macintosh 68040; 16MB RAM; System 7.0 or higher; 640 x 480 display; and double speed CD-ROM drive
System requirements: MPC compliant; 486 processor; 16MB RAM; Windows 95 or higher; 256 color display; sound card; double speed CD-ROM drive; and mouse required
Keywords: Infection Control -- methods; Surgical Wound Infection -- prevention & control